The regulative lock-in: the challenge of establishing Sami fisheries governance in Norway - Johnsen, Jahn Petter; Søreng, Siri Ulfsdatter (Maritime Studies, 2018)
This is a post-peer-review, pre-copyedit version of an article published in Maritime Studies . The final authenticated version is available online at: https://doi.org/10.1007/s40152-018-0119-3 . For almost 30 years, the Sami Parliament has worked to gain influence in the Norwegian fisheries governing system in order to secure Sami fisheries as the material basis of Sami culture. Due to developments in international law and their implementation in state law, the Sami Parliament has gained formal access to the country’s fisheries governance decision-making process. This paper addresses the challenges for a Sami fisheries approach to gain influence in the national governance system. A major issue relates to differences between the institutional design of the Norwegian system, with ecosystem health, profitability and individual welfare as main concerns, while important pillars formulated by the Sami Parliament are subsidiarity and collective rights. In this article, we discuss what might be the way forward for a Sami fisheries policy to expand within the Norwegian fisheries governance system.